2000
DOI: 10.1097/00005176-200002000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intrahepatic Chemotherapy to Treat Advanced Pediatric Hepatic Malignancies

Abstract: Intrahepatic arterial chemotherapy therapy can halt the progression and possibly down-stage advanced pediatric hepatic malignancies. This therapy can also be used as a successful adjunct in altering a patient's chance for successful liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…As the best cure rates have been shown with surgical resection and transplantation, all efforts should be made to make these options available for pediatric patients with HCC . While several groups have reported that TACE is feasible in children, the published experience is limited primarily to small case series of patients with HB, not HCC . Our experience with HCC is similar to the HB TACE literature, in which patients were generally bridged to surgical resection and had a low incidence of severe complications …”
Section: Discussionmentioning
confidence: 54%
“…As the best cure rates have been shown with surgical resection and transplantation, all efforts should be made to make these options available for pediatric patients with HCC . While several groups have reported that TACE is feasible in children, the published experience is limited primarily to small case series of patients with HB, not HCC . Our experience with HCC is similar to the HB TACE literature, in which patients were generally bridged to surgical resection and had a low incidence of severe complications …”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, in our case, a single course of chemoembolization arrested tumor growth, followed by involution of the liver to normal. In both series reporting on the use of hepatic chemoembolization in children with primary liver tumors, multiple cycles were administered with no significant toxicity 13,14. Moreover, in the report by Malogolowokin et al, plasma levels of cisplatinum and doxorubicin were undetectable following HACE in all the pediatric patients sampled, suggesting significant first pass metabolism of the drugs in the liver, and accounting perhaps for the minimal systemic toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple cycles were administered with minimal toxicity. Five of eleven patients were rendered eligible for orthoptic liver transplantation (OLT) following this treatment 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their tumors are typically partially responsive to chemotherapy, and the children have typically undergone four or more cycles of chemotherapy prior to transplantation [42]. Intrahepatic arterial chemotherapy may provide additional benefits [43]. Postoperative attention to the risk of recurrent or metastatic disease is extremely important.…”
Section: Hepatic Malignancymentioning
confidence: 99%